Ivana Manic: Practicum for the sociology of childhood, The Academy of Applied Preschool Teaching and Health Studies, Department of Preschool Teacher Training Studies Kruševac, 2023. - Vujičić, Boban M. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2024)
.